The Causes of Richie Tenenbaum’s Suicide Attempt in The Royal Tenenbaums - Steffanie Preiffer (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
This thesis discussed suicide action in a dramedy movie. In the movie, the decision of suicide begins with negative experiences in childhood which is experienced by Richie, one of the male characters in The Royal Tenenbaums. The purpose of this thesis is to show Richie’s negative self-schema which exists during his childhood, influences how he sees himself and his surroundings. In addition, this thesis exists to reveal the reasons why Richie decides to attempt suicide in his adult life. The theory of negative self-schema shows that Richie’s negative self-schema exists during his childhood is because of divorced parents and criticism. The interpersonal theory of suicide reveals that Richie’s situation matches the criteria of someone who is able to kill himself. First, Richie sees himself as burden to others because he falls into self-hatred perspective and liability. Second, he has faced loneliness, the feeling of lack of reciprocal relationship, and the feeling of social disconnectedness which makes him has a low belongingness. Lastly, these situations make have the ability to do self-harm and strong desire to die. Those steps lead Richie to attempt suicide. Through this analysis, I found that self-esteem and social support give a strong impact for someone’s suicide decision. Keywords: Suicide attempt, negative self-schema, perceived burdensomeness, low belongingness, self-harm